RANCANG BANGUN WEBSITE FORUM KOMUNITAS PECINTA FILM DRAMA KOREA - Ester Cherin Rahardianti, Kartika Imam Santoso, Sugeng Wahyudiono (TRANSFORMASI, 2020)
A discussion is a process of exchanging ideas or thoughts between two or more people that aims to solve an existing problem. Along with the development of discussion technology can be done online. Korean drama lovers usually use social media as a means of online discussion. But on social media Korean drama lovers often still find it difficult when searching for information because there are no category facilities so the topics to discuss in the discussion become irregular. The purpose of this research is to help make it easier for Korean drama lovers to find the information necessary in the creation of this information system using PHP and My SQL programming as a database. The system development method used is Waterfall method with UML as system design model. The result of this research is a web-based online discussion forum for Korean drama lovers that makes it easy for its members to exchange and search for information.